A novel leader election algorithm based on resources for ring networks. (23rd April 2018) - Biswas, Tarun; Bhardwaj, Rajat; Ray, Anjan Kumar; Kuila, Pratyay
Summary: The leader node in a distributed computing system is responsible to establish coordination among all other nodes that are situated apart geographically. Selection of a suitable leader is one of the major and challenging problems. In this paper, a novel leader election algorithm is proposed based on resources of each node in a ring network. All the nodes compute resource strength values by considering available resources like CPU, memory capacity, and residual energy. A node with the highest resource strength over the network is elected as the leader. The proposed algorithm has also considered sudden failure of the nodes particularly when it is the leader node. Moreover, addition of new nodes is also considered. The proposed algorithm shows improvement on message complexity over the network and resource‐based priority generation, which helps in efficient election of the leader. To validate, the proposed algorithm is extensively simulated as well as real‐life hardware experiment is also done. In the experiment, 2 cases are considered with different weight of the resources, and consequent effects are shown. The results are also compared with the existing algorithms, and it is observed that the proposed work comparably performs better that the existing related algorithms. Abstract : A novel leader election algorithm is proposed based on resources (like CPU, memory capacity, and residual energy) of each node in a ring network. The proposed algorithm elects a node as the leader, which has the highest resource strength over the network by transmitting lesser number of messages. Sudden failures of nodes as well as joining of new nodes are also considered. The proposed algorithm is extensively simulated as well as real‐life hardware experiment is also done.